Glass [videorecording (Blu-Ray)] - Shyamalan, M. Night; Shyamalan, M. Night; Shyamalan, M. Night; McAvoy, James, 1979-; Willis, Bruce, 1955-; Jackson, Samuel L (Universal Pictures Home Entertainment, 2021)
When David Dunn, a security guard with superhuman gifts, is sent to a mental institution, he must contend with his archenemy Mr. Glass and Kevin Wendell Crumb, also known as "The Horde" for his multiple personalities, along with a psychiatrist trying to prove they do not have superhuman abilities.